INDICATOR OF DYSCIRCULATORY ENCEPHALOPATHY IN HYPOTHYROIDISM - Khayrullaeva Dilnora Khislatovna (International Journal of Human Computing Studies, 2020)
In the scientific literature there are works devoted to the study of certain aspects of hemodynamics in hypothyroidism, but there is a lack of information about the features of cerebral circulation in conditions of deficiency of thyroid hormones. The aim of our study was to identify discirculatory encephalopathy and factors affecting its development in various forms of hypothyroidism.